The colour stability of natural blue dye extracted from Clitoria ternatea L. in poly(acrylamide-co-acrylic acid) coating film. Issue 4 (1st July 2019) - Abidin, Z.H.Z.; Manah, N.S.A.; Hadi, A.N.; Saugi, N.S.; Fuad, F.A.; Mazni, N.A.; Hassan, H.C.; Careem, M.A.; Arof, A.K.
Abstract : Purpose: This paper aims to focus on a comparison study of the visible stability of natural blue dye consisting anthocyanin molecules extracted from Clitoria ternatea in coating films. Design/methodology/approach: The coating films were prepared by mixing the blue dye with poly(acrylamide-co-acrylic acid) in three different weight ratios. Samples were coded as 10PBA, 15PBA and 20PBA, where PBA is the abbreviation for poly acrylamide-co-acrylic acid, blue dyes and anthocyanin. The number at the beginning of each code represents the weight percentage of poly(acrylamide-co-acrylic acid) to natural blue dye. The mixtures were applied on separate glass substrates to form coating films. Another set of samples were prepared for the comparison study with a commercial acrylic clear coat (cc) applied on the surface of the 10PBA, 15PBA and 20PBA coating films. These coating films were coded 10PBAcc, 15PBAcc and 20PBAcc. The purpose of the clear coat is to observe how it affects the colour stability of the blue coating films with respect to time. All samples were exposed to the ultraviolet (UV) source, an 18 W Philips TL-D 18w/830 UV fluorescent lamp. The UV lamp was placed 15 cm above the surface of the samples for 35 days. The colour of the coatings was measured using CIE L*a*b* colour space coordinate. Findings: The results obtained show 10PBA and 10PBAcc have the highest colour stability after 35 days of exposure to UV light. The reflectivity of the coating films was also measured during exposure to UV lamp. Reflectivity measurements also showed that 10PBA and 10PBAcc coating films had the highest reflective stabilities. Research limitations/implications: The potential of using natural blue dye consisting anthocyanin in coating film to obtain high colour stability. Practical implications: The coating film developed in this work is suitable to be applied on glass substrates. Originality/value: The application of anthocyanin dye extracted from the Clitoria ternatea L. as a colourant in coating films